Effects of word class and training method on vocabulary learning in a second language - Ludington, Jason D. (Research in Language, 2015)
It is not fully known whether nouns or verbs are easier to learn in a second language. A noun learning advantage has been observed for children in many languages (e.g., Gentner, 1982), but few have examined whether mature second language learners show a similar pattern. In the current study 84 university students were trained with nonce words for 96 familiar, concrete concepts (half nouns, half verbs), half labeled ostensibly, and half in contexts that allowed label meanings to be inferred. Vocabulary knowledge was assessed through recognition tests after a delay of either five minutes or one week. No evidence of a word class advantage was found—participants did not demonstrate a noun advantage. Ostensive training was superior to inferential training at five minutes but not after one week.